2006
DOI: 10.1037/0021-9010.91.1.109
|View full text |Cite
|
Sign up to set email alerts
|

You can take it with you: Individual differences and expatriate effectiveness.

Abstract: The authors report the collaborative efforts of 2 research teams that independently investigated the effects of stable personality traits (the Big Five) and specific behavioral competencies (cultural flexibility, task and people orientations, and ethnocentrism) on key dimensions of expatriate effectiveness: psychological adjustment, assignment withdrawal cognitions, and job performance. Analyses of multiple-source and longitudinal data from 3 studies, including a diverse sample of expatriates in Hong Kong and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
507
4
17

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(570 citation statements)
references
References 77 publications
21
507
4
17
Order By: Relevance
“…This finding shows the strong relationship that has already been proven in previous studies between personality characteristics and adjustment (Huang et al, 2005;Shaffer et al, 2006). In addition, all the measures of adjustment to a foreign culture were found related to one another in significant positive relationships but in lower than expected correlations.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding shows the strong relationship that has already been proven in previous studies between personality characteristics and adjustment (Huang et al, 2005;Shaffer et al, 2006). In addition, all the measures of adjustment to a foreign culture were found related to one another in significant positive relationships but in lower than expected correlations.…”
Section: Discussionsupporting
confidence: 82%
“…In the research studies conducted on populations of expatriates on lengthy international assignments positive relations were found between the characteristics of openness (Huang et al, 2005;Raduan et al, 2010;Shaffer et al, 2006), agreeableness, and extraversion (Caligirui, 2000;Huang et al, 2005;Shaffer et al, 2006) and level of adjustment to a foreign culture. However, established relations were not found between the traits of conscientiousness and neuroticism and the level of adjustment to a foreign culture (Caligiuri, 2000;Huang et al, 2005).…”
Section: Personality and Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of literature indicated individual differences such as self-monitoring personality (Caligiuri & Day, 2000), gender (Sinangil & Ones, 2003), non-ethnocentrism (Hechanova et al, 2003, Big Five Personality (Mol et al, 2005), communicational ability, relational ability, stress tolerance (Holopainen & Bjorkman, 2005), cultural flexibility (Shaffer et al, 2006), task and people orientation (Shaffer et al, 2006), goal orientation (Wang & Takeuchi, 2007) and previous international experience (Varma et al, 2006) related to expatriate job performance.…”
Section: Job Performancementioning
confidence: 99%
“…Although expatriates are increasingly becoming "key persons" for MNCs, the process of assigning an expatriate abroad is not a simple matter (Shaffer et al 2001;Shaffer et al 2006). How to select expatriates who have abilities to adjust in the new environment becomes one important issue of the work force management at MNCs.…”
Section: Introductionmentioning
confidence: 99%